KETERLIBATAN PENEGAK HUKUM TERHADAP PENJEMPUTAN PAKSA PERSPEKTIF PERLINDUNGAN ANAK : Studi Kasus Selebgram Laura Meizani (Loly) - Fikriyah, Durrotul; Dewi, Dwi Ratna Cinthya; Qudsiyah, Salma Nafisatul; Ningsih, Marlinda Ayu; Romadiyah, Siti Nurul (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2024)
This research analyzes the involvement of law enforcement in the forced pick-up carried out by Nikita Mirzani’s daughter named Laura Meizani (Loly) .This case is very trending on social media for a couple of days, so the author is interested in making it as the object of the latest research regarding the forced pick-up that Nikita Mirzani carried out on her child. This research uses a normative law research method with a statutory approach related to this issue. The research results explained that: 1. The forced pick-up carried out by Nikita Mirzani involving law enforcement was in accordance with applicable legal provisions. 2. Even though the authorities state that they have complied with procedures, it is best to pay more attention when picking up minors, especially those who are public figures or celebrities, to maintain the child's safety and comfort.